Hybrid constructed wetlands for the treatment of wastewater from a fertilizer manufacturing plant: Microcosms and field scale experiments - Maine, Maria Alejandra (2019)
Wastewater from a fertilizer manufacturing plant requires improvement prior to its environmental disposal. Ammonium is the critical contaminant to be removed. The aim of this study was to evaluate the feasibility of using free water surface wetlands (FWSWs), horizontal subsurface flow wetlands (HSSFWs), and their combination in hybrid wetlands (HWs) for the final treatment of wastewater with high ammonium concentration from a fertilizer manufacturing plant. Substrates and macrophytes were evaluated in microcosm experiments during three months. There were no significant differences in contaminant removal among HSSFWs with LECA or FWSWs planted with Typha domingensis or Canna indica. In a second stage, two configurations of pilot-scale HWs were constructed at the manufacturing facilities. Configuration A: HSSFW(A1)-FWSW(A2) and Configuration B: FWSW(B1)-HSSFW(B2) were evaluated during 12 months. There were no significant differences in contaminant removal (%) between the two configurations of HWs for COD (A: 74.5 ± 12.2/B: 81.5 ± 9.4), ammonium (A: 59.5 ± 17.5/B: 57.9 ± 21.4), nitrite (A: 79.8 ± 24.2/B: 80.6 ± 16.8) and dissolved inorganic nitrogen (DIN) (A: 59.4 ± 17.3/B: 50.3 ± 24.4). However, nitrate concentration (9.83 ± 3.11 mg N L−1) was significantly lower after Configuration A than after Configuration B (18.8 ± 5.2 mg N L−1). Comparing FWSWs and HSSFWs, they did not present significant differences in ammonium removal, while FWSWs presented the highest DIN removal. T. domingensis and C. indica in HSSFWs and T. domingensis in FWSWs tolerated wastewater conditions. T. domingensis presented the highest productivity. In further research, FWSWs in series planted with T. domingensis should be studied.